Teacher variables and problem-solving difficulties in college algebra among teacher education students in Davao City - Rellon, Louie Resti Sandoval (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to determine the relationship between teacher variables and problem-solving difficulties in Algebra courses among teacher education students in Davao City. Using a descriptive correlational approach, this study involved 196 randomly selected students. Data were collected through a validated questionnaire and analyzed using descriptive statistics, t-test for independent groups, Pearson r correlation, and multiple regression analysis. The results showed a significant relationship between teacher variables, especially motivational and aversive behaviors, and problem-solving difficulties, particularly in motivation, flexibility, and visualization. Aversive teacher behaviors were the main predictor of several aspects of problem-solving difficulties. This study has implications for positive interactions between teachers and students in supporting mathematical thinking skills. The finding informs teacher training to boost student motivation. These results highlight the need to address negative teacher behaviors in improving students’ problem-solving performance.